Local academic knowledge spillovers and the concentration of economic activity - Attila Varga (European Regional Science Association (ERSA), 1998)
Agglomeration effects on the intensity of local knowledge spillovers from universities to high technology innovations are examined within the modified Griliches-Jaffe knowledge production function framework. Estimations are carried out at the level of US metropolitan areas. Concentration of high technology employment turns out to be the most important factor promoting local academic knowledge spillovers. It is found that a ?critical mass? of agglomeration needs to be reached in order to expect substantial local economic effects of academic research spending. (JEL O31, H41, O40)
Keywords: 330